2015
DOI: 10.1096/fj.15-270462
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of serum- and glucocorticoid-inducible kinase 1 enhances TLR-mediated inflammation and promotes endotoxin-driven organ failure

Abstract: Serum-and glucocorticoid-regulated kinase (SGK)1 is associated with several important pathologic conditions and plays a modulatory role in adaptive immune responses. However, the involvement and functional role of SGK1 in innate immune responses remain entirely unknown. In this study, we establish that SGK1 is a novel and potent negative regulator of TLR-induced inflammation. Pharmacologic inhibition of SGK1 or suppression by small interfering RNA enhances proinflammatory cytokine (TNF, IL-12, and IL-6) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
3
33
0
1
Order By: Relevance
“…Interestingly, the activation state of SGK1, which we have recently established to be a potent anti-inflammatory mediator in the context of TLR-engagement, 3 was also enhanced by MaR1, RVD1 and RVD2. However, the phosphorylation state of SYK, a TLR ligand and inflammatory enhancer, 43 and several MAPK-related molecules was not influenced by resolvins.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, the activation state of SGK1, which we have recently established to be a potent anti-inflammatory mediator in the context of TLR-engagement, 3 was also enhanced by MaR1, RVD1 and RVD2. However, the phosphorylation state of SYK, a TLR ligand and inflammatory enhancer, 43 and several MAPK-related molecules was not influenced by resolvins.…”
Section: Discussionmentioning
confidence: 87%
“…The activation status of SGK1, an anti-inflammatory kinase, 3 was similarly enhanced. Phosphorylation of SYK, a TLR ligand and inflammatory enhancer, 43 pERK1/2, pSAPK/JNK and/or p38 MAPK were unaffected (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…Since SGKs are implicated in inflammatory responses in some immune cells [13,14], we tested whether they play a role in microglial activation and inflammatory responses. In BV-2 cells stimulated with LPS, we found that the levels of gene expression of inflammatory mediators, iNOS and TNFα, were upregulated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that inflammatory factors are facilitated by SGK inhibition and that NF-κB signaling is regulated by SGK1 in other immune cells [13,14], we inspected the effect of SGK inhibition on NF-κB signaling. First, we probed nuclear translocation of NF-κB by LPS application and found that fluorescent signals of NF-κB seemed to be more intensive in nuclei in the presence of gsk650394 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation